Comparison of levetiracetam versus phenytoin/fosphenytoin for busulfan seizure prophylaxis at a pediatric institution. (24th April 2021) - Hughes, Kaitlynn; Garrity, Lisa; Nelson, Adam S.; Lane, Adam; Teusink‐Cross, Ashley
Abstract: Introduction: Busulfan is a chemotherapy agent used in hematopoietic stem cell transplant (HSCT) conditioning regimens. Busulfan is associated with tonic‐clonic seizures in ~10% of patients if administered without seizure prophylaxis. Historically, phenytoin was the most commonly utilized seizure prophylaxis agent; however, phenytoin is associated with CYP450 drug interactions and potentially increases the clearance of busulfan. Levetiracetam is being used more recently for busulfan seizure prophylaxis and is not associated with drug‐drug interactions; however, data supporting use in pediatric patients are limited. The primary objective is to determine whether there is any difference in seizure rates or safety profile between phenytoin and levetiracetam when used for seizure prophylaxis. Methods: We conducted a retrospective chart review including patients who received busulfan between 2010 and 2019 were identified. The data were evaluated to compare the incidence of busulfan‐induced seizures in HSCT patients receiving either phenytoin or levetiracetam and to determine the impact of drug‐drug interactions on treatment outcomes/adverse events. Results: A total of 342 patients were included with a median age of six years. Overall, five patients within the phenytoin group (n = 126) (4%) and zero patients in the levetiracetam group (n = 216) experienced a seizure ( P  = .007). There were no differences in liver enzyme elevations, recurrence rates of primary disease, and veno‐occlusive disease. Conclusion: Levetiracetam is effective at preventing seizures associated with busulfan administration with no clinically significant adverse effects when compared to phenytoin.